2015
DOI: 10.30539/iraqijvm.v39i2.169
|View full text |Cite
|
Sign up to set email alerts
|

The protective role of alcoholic extract of (Anethum graveolens) seeds on renal function in alloxan induced diabetic rabbits

Abstract:      This study was designed to investigate the effect of dill (Anethum graveolens) seeds in mitigating the complications of induced diabetes mellitus such as nephropathy of adult female rabbits. Thirty adult female rabbits were randomly assigned to 5 equal groups and treated daily for 45 days as follows: Control group (C) drenched tap water, control group intubated orally with 700 mg/kg B.W ethanolic extract of dill (T1), diabetic group drenched tap water (T2), diabetic group intubated orally700 mg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A. graveolens , known as sheviid in ITM, has been widely utilized to reduce renal swelling [ 32 , 33 ]. Khalil et al indicated that oral ingestion of alcoholic extract of A. graveolens seeds in diabetic treated animals by alloxan diminished serum urea and creatinine and increased the serum glutathione concentration [ 48 ]. Kim et al showed that the methanolic extract of A. graveolens flowers suppressed inducible nitric oxide synthase (iNOS) and inhibited NF- κ B activity via inhibiting the phosphorylation of serine/threonine kinase 1 (Akt) in lipopolysaccharide (LPS)-stimulated RAW 264.7 cells.…”
Section: Resultsmentioning
confidence: 99%
“…A. graveolens , known as sheviid in ITM, has been widely utilized to reduce renal swelling [ 32 , 33 ]. Khalil et al indicated that oral ingestion of alcoholic extract of A. graveolens seeds in diabetic treated animals by alloxan diminished serum urea and creatinine and increased the serum glutathione concentration [ 48 ]. Kim et al showed that the methanolic extract of A. graveolens flowers suppressed inducible nitric oxide synthase (iNOS) and inhibited NF- κ B activity via inhibiting the phosphorylation of serine/threonine kinase 1 (Akt) in lipopolysaccharide (LPS)-stimulated RAW 264.7 cells.…”
Section: Resultsmentioning
confidence: 99%